ELEMEN KLASTER INDUSTRI PENGOLAHAN SUSU DI DAERAH ISTIMEWA YOGYAKARTA - Nur Laili Marufah; Tri Djoko Wisnumurti; Budi Guntoro (Buletin Peternakan, 2015)
This research was conducted to study the elements and value chain of milk-processing cluster industry in Daerah Istimewa Yogyakarta. The respondent in this study consisted of cow and goats milk processing industry, dairy cooperative and related institution. The data consisted of primary data and secondary data. Primary data were collected through observation and interviews, while secondary data obtained from statistical data from Department of Industry, Trade and Cooperatives, Agricultural Service of Agriculture Department and LPPOM MUI DIY. Descriptive analysis were used in this study to analyzed the data. Respondent and locations were determined using purposive sampling methods lead to be analyse descriptively. The results showed that stakeholders involved as important elements of milkprocessing cluster industry were milk suppliers (farmer, dairy groups, and cooperative), core industry (small-medium scale processor of cow’s and goat milk), supporting industry (sugar, packaging and tools), supporting institution (bank, university, and government agencies), related industry (food chain, bakery, and coffee shop), and also buyers (retailer, distributor, end user or consumer). Their main products are pasteurized cow’s and goat milk, yoghurt of cow’s milk, and goat milk powder. The long chains to produce milk product since the raw milk have indicated some added values on economy and involvement of man powers leading to local economic development as well as of technology innovation or industry. It has been concluded that milk-processing cluster industry could be used as a locomotive for regional economics development.(Key words: Daerah Istimewa Yogyakarta, Elements, Milk-processing cluster industry, Regional economic development, Value chain)